Synthesis method and application of thermo-sensitive aqueous electrolyte
By adding Poloxamer as an additive to the aqueous zinc ion battery electrolyte, the temperature-sensitive aqueous electrolyte is prepared, which solves the problem of poor operating stability of the battery at extreme temperatures and achieves efficient ion transport and stable circulation in a wide temperature range.
Patent Information
- Application Number
- CN202510035835.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-01
AI Technical Summary
Water-based zinc ion batteries have poor operating stability at extreme temperatures, high temperature accelerates moisture evaporation and side reactions, and low temperature hinders ion transport, resulting in a decline in electrochemical performance.
Poloxamer was used as the electrolyte additive, and the temperature-sensitive aqueous electrolyte was prepared by adding Poloxamer to the zinc brine solution and mechanically stirring under different temperature conditions.
The electrolyte exhibits a unique solution-gel conversion behavior in a wide temperature range, keeping liquid in low temperatures and converting into gel at high temperatures, effectively inhibiting moisture evaporation and side reactions, and improving cycle stability and wide temperature adaptability.
Smart Images

Figure CN119742468A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a synthesis method of a temperature-sensitive aqueous electrolyte and application thereof. Background Art
[0002] Aqueous zinc-ion batteries (AZIBs) are attractive candidates for their low cost, safety, environmental sustainability, and high theoretical capacity of the zinc anode (820 mAh g −1 and 5855 mAh cm −3 ) and low reduction potential (−0.76 V, relative to standard hydrogen electrode) are considered as promising candidate technologies for large-scale energy storage. However, the high reactivity of solvent H2O leads to severe hydrogen evolution reaction (HER) on the surface of zinc anode, which in turn aggravates interfacial corrosion, byproduct formation and zinc dendrite growth, which together deteriorate battery performance. More importantly, the stable operation of AZIBs at extreme temperatures is a huge challenge. Specifically, high temperature accelerates thermodynamic and kinetic processes and enhances water evaporation and side reactions, while low temperature hinders ion transport, resulting in a decrease in the electrochemical performance of AZIBs.
[0003] To achieve wide temperature performance of AZIBs, the intrinsic activity of water in aqueous electrolytes must be suppressed without reducing ion transport. To this end, several electrolyte engineering strategies have been proposed, including high-concentration electrolytes, solid or quasi-solid electrolytes, organic-inorganic hybrid electrolytes, and additive strategies. High-concentration electrolytes restrict free water by high salt / water molar ratios, which inhibits HER, but these electrolytes have high viscosity at low temperatures due to limited ion transport. Solid or quasi-solid electrolytes provide a physical barrier against leakage and suppress the formation of zinc dendrites, but their low ionic conductivity and interfacial resistance limit high-rate performance. Although organic-aqueous hybrid electrolytes exhibit a wider electrochemical stability window and better wide temperature performance, the hybrid formulations including organic solvents increase cost, increase flammability, and have poor stability at high temperatures.
[0004] In contrast, the electrolyte additive strategy is considered a promising approach due to its advantages of simplicity, operability, and cost-effectiveness. Electrolyte additives in AZIBs have multiple functions, including regulating the solvation structure, changing the hydrogen bonding network, forming adsorption layers, generating electrostatic shielding effects, and constructing a solid electrolyte interface (SEI). Although additive engineering has significantly improved the performance of AZIBs, additives that can extend the operating temperature range of the electrolyte are still needed. At high temperatures, water evaporation and increased side reactions can reduce the cycling stability of the zinc anode; this problem can be solved by forming a gel structure in the electrolyte to limit water migration. In contrast, in environments below 0 °C, traditional aqueous electrolytes tend to freeze, resulting in weakened ion transport and sluggish electrochemical kinetics. Keeping the electrolyte liquid at low temperatures can alleviate these problems. Therefore, achieving a wide temperature range operating system requires maintaining efficient ionic conductivity at low temperatures while maintaining stability at high temperatures. Introducing an additive that keeps the electrolyte liquid at low temperatures and transforms it into a gel state at high temperatures can simultaneously meet the performance requirements under both conditions. Therefore, thermosensitive polymers are undoubtedly excellent candidates for this role. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for synthesizing a temperature-sensitive aqueous electrolyte which is simple to operate, low in production cost and easy to industrialize.
[0006] Another technical problem to be solved by the present invention is to provide an application of the temperature-sensitive aqueous electrolyte.
[0007] In order to solve the above problems, the present invention provides a method for synthesizing a temperature-sensitive aqueous electrolyte, characterized in that: the method is to dissolve zinc salt in deionized water, and ultrasonically stir it at room temperature to obtain a concentration of 1-3 mol L −1 a zinc salt aqueous solution; poloxamer is added to the zinc salt aqueous solution, and mechanical stirring is performed at 0°C. After stirring evenly, a temperature-sensitive aqueous electrolyte is obtained.
[0008] The zinc salt is one of zinc trifluoromethanesulfonate (Zn(OTf)2), zinc chloride (ZnCl2), zinc perchlorate (Zn(ClO4)2), zinc bromide (ZnBr2) or zinc nitrate (Zn(NO3)2).
[0009] The ultrasonic stirring time is 20 to 30 minutes.
[0010] The poloxamer is one of Poloxamer 124, Poloxamer 182, Poloxamer 188, Poloxamer 331 or Poloxamer 407, and the mass fraction of the poloxamer in the electrolyte is 15-30%.
[0011] The mechanical stirring condition refers to a stirring speed of 300-500 r min −1 , stirring time is 12~24 h.
[0012] A temperature-sensitive aqueous electrolyte synthesized by the method described above.
[0013] The application of the temperature-sensitive aqueous electrolyte as described above is characterized in that the electrolyte is used in zinc ion batteries.
[0014] The zinc ion battery is one of a zinc||zinc symmetrical battery, a zinc||copper asymmetrical battery or a zinc||vanadium pentoxide full battery.
[0015] Compared with the prior art, the present invention has the following advantages: 1. The present invention can significantly improve the cycle stability, side reaction inhibition ability and wide temperature adaptability of zinc ion batteries by introducing poloxamer as an electrolyte additive. Poloxamer is a non-ionic block copolymer composed of alternating hydrophilic polyoxyethylene (PEO) and hydrophobic polyoxypropylene (PPO) blocks. By mixing poloxamer with a zinc-based aqueous electrolyte in an appropriate proportion under low temperature conditions, a uniform modified electrolyte can be prepared, which is simple and efficient to operate.
[0016] At room temperature, Poloxamer can act as a solvation restructuring agent and water cluster regulator. Its molecules reconstruct the hydrogen bond network through interaction with water molecules and promote the trifluoromethanesulfonate (OTf − ) Embedded Zn 2+ This effect can significantly enhance the stability of water molecules and reduce their activity, thereby effectively inhibiting side reactions such as hydrogen evolution reaction and forming a solvation shell composed of OTf −The decomposed organic-inorganic composite solid electrolyte interface (SEI) further optimizes the surface stability of the zinc negative electrode and the zinc deposition behavior. It is particularly noteworthy that the temperature-sensitive properties of Poloxamer enable the electrolyte to exhibit a unique solution-gel transition behavior over a wide temperature range. Under low temperature conditions, the electrolyte containing an appropriate amount of Poloxamer can remain in a liquid state to ensure the efficiency of ion transfer; while under high temperature conditions, the hydrophobic segments in the Poloxamer molecular chains will aggregate to form micelles, which will further interweave and cross-link, thereby capturing water in the gel network, effectively preventing water evaporation and maintaining normal operation of the battery. This characteristic enables the modified electrolyte to exhibit excellent reversibility and stability in a wide temperature range of -30 ℃ to 60 ℃, effectively solving the problem of evaporation of traditional electrolytes at high temperatures and limited ion transfer at low temperatures. At the same time, this modified electrolyte can meet the operating requirements under a wide temperature environment while significantly reducing costs, showing excellent practical value and commercial potential.
[0017] 2. The present invention is simple to operate, has low production cost, is environmentally friendly, is easy to industrialize, and the composition and performance of the obtained electrolyte are highly adjustable.
[0018] 3. The electrolyte obtained by the present invention is applied to zinc ion batteries, which can show excellent wide temperature compatibility and performance improvement. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0020] Figure 1 This is the thermosensitive property of the electrolyte prepared in Example 1 of the present invention.
[0021] Figure 2 This is a graph showing the constant current charge and discharge test results when the electrolyte prepared in Example 1 of the present invention is applied to a zinc||zinc symmetrical battery.
[0022] Figure 3 This is a graph showing the coulombic efficiency test results when the electrolyte prepared in Example 1 of the present invention is applied to a zinc||copper asymmetric battery.
[0023] Figure 4 This is a graph showing the charge and discharge test results when the electrolyte prepared in Example 1 of the present invention is applied to a zinc||vanadium pentoxide full battery.
[0024] Figure 5 This is a comparison chart of liquid H NMR spectra of the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1.
[0025] Figure 6This is a comparison of the liquid infrared spectra of the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1. The left figure is the infrared spectrum corresponding to S=O; the right figure is the infrared spectrum corresponding to CF.
[0026] Figure 7 This is a comparison diagram of the X-ray photoelectron spectra of SEI on the surface of the zinc sheet after circulation in the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1.
[0027] Figure 8 Linear sweep cyclic voltammetry (LSV) diagrams of the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1.
[0028] Fig. 9 This is a comparison chart of the heating water retention experiment of the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1.
[0029] Fig.10 The zinc||zinc symmetric battery assembled with the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1 was charged at 30°C and 1.0 mA cm −2 , 1.0 mAh cm −2 Surface micromorphology of the zinc sheet after cycling for 100 h under the same conditions. DETAILED DESCRIPTION
[0030] A method for synthesizing a temperature-sensitive aqueous electrolyte, comprising dissolving a zinc salt in deionized water, stirring the solution with ultrasonic waves at room temperature for 20 to 30 minutes, and obtaining a solution with a concentration of 1 to 3 mol L −1 Poloxamer was added to the zinc salt aqueous solution and mechanically stirred at 0 °C at a speed of 300-500 r min −1 , stirring time is 12~24h. After stirring evenly, the temperature-sensitive aqueous electrolyte is obtained.
[0031] Wherein: the zinc salt is one of zinc trifluoromethanesulfonate (Zn(OTf)2), zinc chloride (ZnCl2), zinc perchlorate (Zn(ClO4)2), zinc bromide (ZnBr2) or zinc nitrate (Zn(NO3)2).
[0032] The poloxamer is one of Poloxamer 124, Poloxamer 182, Poloxamer 188, Poloxamer 331 or Poloxamer 407, and the mass fraction of the poloxamer in the electrolyte is 15-30% (mass unit is g).
[0033] Poloxamer is a type of nonionic block copolymer, whose structure is composed of alternating hydrophilic polyoxyethylene (PEO) and hydrophobic polyoxypropylene (PPO) blocks. Its general structural formula can be expressed as: HO-(CH2CH2O) a -(CH2CHCH3O) b -(CH2CH2O) a -H Among them: the substituent is CH2CH2O: hydrophilic polyoxyethylene (PEO) unit; CH2CHCH3O: hydrophobic polyoxypropylene (PPO) unit.
[0034] The specific structure is shown in Table 1: Table 1 Poloxamer structure Application of a temperature-sensitive aqueous electrolyte: The electrolyte is used in a zinc ion battery. The zinc ion battery is one of a zinc||zinc symmetric battery, a zinc||copper asymmetric battery or a zinc||vanadium pentoxide full battery.
[0035] The battery consists of a positive electrode, a negative electrode, a separator and an electrolyte, and is assembled into a CR2032 button cell. Among them: the negative electrode is a zinc sheet, the separator is a glass fiber, and the positive electrode is a zinc sheet, a copper foil, and a vanadium pentoxide, respectively, which are assembled into a zinc||zinc symmetrical battery, a zinc||copper asymmetric battery, and a zinc||vanadium pentoxide full battery.
[0036] The specific process is as follows: Drop 100 μL of electrolyte on the glass fiber, assemble the battery in the order of negative electrode shell-negative electrode-diaphragm-electrolyte-positive electrode-gasket-shrapnel-positive electrode shell, and use a manual packaging machine for pressure packaging.
[0037] Example 1 A method for synthesizing a temperature-sensitive aqueous electrolyte, comprising dissolving Zn(OTf)2 in deionized water, stirring the solution with ultrasonic wave at room temperature for 20 to 30 minutes, and obtaining a solution with a concentration of 2 mol L −1 Zn(OTf)2 aqueous solution; 20% of Poloxamer 407 solid was added to the Zn(OTf)2 aqueous solution, and mechanical stirring was performed at 0 ℃ with a stirring speed of 300 rmin −1 , stirring time is 12 h. After stirring evenly, a temperature-sensitive aqueous electrolyte is obtained. The electrolyte exhibits obvious heat-sensitive properties, such as Figure 1 As shown, it is in a liquid state at low temperatures, but becomes a gel state as the temperature rises, and this process is reversible.
[0038] ⑴ The obtained temperature-sensitive aqueous electrolyte was applied to the Zn||Zn symmetric battery. The assembled Zn||Zn symmetric battery was subjected to constant current charge and discharge test at an appropriate current density and surface capacity. −2 , 1.0 mAh cm −2 Under these conditions, the results are as follows Figure 2 As shown in the figure, the Zn||Zn symmetric battery can be stably cycled for more than 4000 h, and the polarization voltage has no obvious change, indicating that its interface stability to the zinc negative electrode is extremely high. −2 , 0.2 mAh cm −2 Under the same conditions, the Zn||Zn symmetric battery can be stably cycled for more than 1000 h. At 60 °C, 0.2 mA cm −2 , 0.2 mAh cm −2 Under these conditions, the Zn||Zn symmetric battery can be cycled stably for more than 850 h.
[0039] (2) The obtained temperature-sensitive aqueous electrolyte was applied to a Zn||Cu asymmetric battery. The assembled Zn||Cu asymmetric battery was tested for coulombic efficiency at an appropriate current density and surface capacity. −2 , 1.0 mAh cm −2 Under these conditions, the results are as follows Figure 3 As shown in Figure 2, the Zn||Cu asymmetric battery can be stably cycled for more than 450 cycles, and the Coulombic efficiency remains at 99.2%, indicating that the reversibility of Zn deposition / stripping is still good. −2 , 0.05 mAh cm −2 Under the same conditions, the Zn||Cu asymmetric battery can be stably cycled for more than 500 cycles. At 60 °C, 0.4 mA cm −2 , 0.2 mAh cm −2 Under these conditions, the zinc||copper asymmetric battery can be stably cycled for more than 80 cycles.
[0040] ⑶ The obtained temperature-sensitive aqueous electrolyte was applied to the zinc||vanadium pentoxide full battery. The assembled zinc||vanadium pentoxide full battery was discharged to 0.2 V at an appropriate current density and then charged to 1.6 V for long cycle charge and discharge test. −1 Under these conditions, the results are as follows Figure 4 As shown in Figure 2, after the full battery has been stably cycled for more than 6000 cycles, it still has a capacity retention rate of 94.2% and has excellent rate performance. −1 Under the same conditions, the full battery still has a capacity retention rate of 90.3% after more than 280 cycles of stable cycling. −1Under these conditions, the full battery still has a capacity retention rate of 94.3% after more than 1,000 cycles of stable cycling.
[0041] Comparative Example 1 Preparation of an aqueous zinc ion battery electrolyte: Dissolve Zn(OTf)2 in deionized water to prepare 2 molL −1 The Zn(OTf)2 aqueous solution is the electrolyte. Compared with Example 1, the only difference is that Poloxamer 407 is not added.
[0042] Figure 5 This is a liquid NMR hydrogen spectrum comparison diagram of the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1. As can be seen from the figure, after the addition of Poloxamer 407, the hydrogen peak in the spectrum moves to the low field, indicating that the introduction of Poloxamer 407 forms new hydrogen bonds and destroys the original hydrogen bond network between water molecules.
[0043] Figure 6 This is a comparison of the liquid infrared spectra of the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1. As can be seen from the figure, after adding Poloxamer 407, the spectrum shifted significantly, indicating that the introduction of Poloxamer 407 promoted the − Enter the zinc ion solvation structure.
[0044] Figure 7 This is a comparison of the X-ray photoelectron spectra of SEI on the surface of the zinc sheet after circulation in the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1. As can be seen from the figure, after adding Poloxamer 407, SEI of zinc fluoride and zinc sulfide is generated, which is beneficial to enhance the zinc ion conductivity and corrosion resistance.
[0045] Figure 8 The linear sweep cyclic voltammetry (LSV) diagrams of the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1. As can be seen from the diagram, after adding Poloxamer 407, the electrochemical window is widened and the hydrogen evolution reaction is suppressed.
[0046] Fig. 9 This is a comparison chart of the heating water retention experiment of the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1. As can be seen from the figure, after adding Poloxamer 407, the water retention capacity of the electrolyte is significantly enhanced, which can ensure the normal operation of the battery even at high temperatures.
[0047] The zinc||zinc symmetric battery assembled with the electrolyte prepared in Example 1 and the electrolyte prepared in Comparative Example 1 was subjected to constant current charge and discharge tests at 30, −30, and 60 °C. At different temperatures, the introduction of Poloxamer 407 greatly prolonged the cycle life.
[0048] The coulombic efficiency of the zinc||copper asymmetric battery assembled with the electrolyte prepared in Example 1 and the electrolyte prepared in Comparative Example 1 was tested at 30, −30, and 60 °C. At different temperatures, the introduction of Poloxamer 407 significantly improved the reversibility of zinc deposition and stripping.
[0049] The zinc||vanadium pentoxide full battery assembled with the electrolyte prepared in Example 1 and the electrolyte prepared in Comparative Example 1 was subjected to long cycle charge and discharge tests at 30, -30, and 60 ° C. At different temperatures, the introduction of Poloxamer 407 significantly improved the capacity retention rate and cycle stability.
[0050] In summary, the introduction of Poloxamer 407 significantly improved the wide temperature compatibility and electrochemical performance of the electrolyte.
[0051] Fig.10 The zinc||zinc symmetric battery assembled with the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1 was charged at 30°C and 1.0 mA cm −2 , 1.0 mAh cm −2 The surface micromorphology of the zinc sheet after 100 h of circulation under the conditions of Poloxamer 407. It can be seen from the figure that the surface of the zinc sheet after circulation in the modified electrolyte containing Poloxamer 407 is smooth and flat, without dendrites; while the surface of the zinc sheet after circulation in the electrolyte of comparative example 1 is uneven, with obvious zinc dendrites. This shows that the introduction of Poloxamer 407 inhibits dendrite growth, reduces the risk of zinc dendrite puncture, and improves interface stability.
[0052] Example 2 A method for synthesizing a temperature-sensitive aqueous electrolyte, comprising dissolving Zn(OTf)2 in deionized water, stirring the solution with ultrasonic wave at room temperature for 20 to 30 minutes, and obtaining a solution with a concentration of 2 mol L −1 Zn(OTf)2 aqueous solution; 25% Poloxamer 331 solid was added to the Zn(OTf)2 aqueous solution and mechanically stirred at 0 °C at a speed of 300 rmin −1 , and the stirring time is 12 h. After stirring evenly, the temperature-sensitive aqueous electrolyte is obtained.
[0053] The obtained temperature-sensitive aqueous electrolyte was applied to batteries. At 30 °C, 1.0 mA cm−2 , 1.0 mAhcm −2 Under the same conditions, the Zn||Zn symmetric battery can be stably cycled for more than 2000 h without significant change in polarization voltage. −2 , 1.0 mAh cm −2 Under these conditions, the zinc||copper asymmetric battery can be stably cycled for more than 300 cycles, and the coulombic efficiency remains above 99.0%. In addition, the surface of the zinc sheet after the cycle is significantly improved due to the introduction of Poloxamer 331 to avoid the formation of dendrites.
[0054] Example 3 A method for synthesizing a temperature-sensitive aqueous electrolyte, comprising dissolving Zn(ClO4)2 in deionized water, stirring the solution with ultrasonic wave at room temperature for 20 to 30 minutes, and obtaining a solution with a concentration of 2 mol L −1 Zn(ClO4)2 aqueous solution; 15% of Poloxamer 188 solid was added to the Zn(ClO4)2 aqueous solution, and mechanical stirring was performed at 0 ℃ with a stirring speed of 300 rmin −1 , and the stirring time is 12 h. After stirring evenly, the temperature-sensitive aqueous electrolyte is obtained.
[0055] The obtained temperature-sensitive aqueous electrolyte was applied to batteries. At -30 °C, 0.2 mA cm −2 , 0.2 mAh cm −2 Under the same conditions, the Zn||Zn symmetric battery can be stably cycled for more than 1500 h. At -30 °C, 0.1 mA cm −2 , 0.05 mAh cm −2 Under the same conditions, the zinc||copper asymmetric battery can be stably cycled for more than 600 cycles, and the coulombic efficiency remains above 99.3%. −1 Under these conditions, the zinc||vanadium pentoxide full battery still has a capacity retention rate of 89.8% after stable cycling for more than 400 cycles.
[0056] Example 4 A method for synthesizing a temperature-sensitive aqueous electrolyte, comprising dissolving zinc chloride in deionized water, stirring the solution with ultrasonic waves at room temperature for 20 to 30 minutes, and obtaining a solution with a concentration of 2 mol L −1 A zinc chloride aqueous solution was prepared; 30% Poloxamer 182 solid was added to the zinc chloride aqueous solution and mechanically stirred at 0 °C at a speed of 300 r min −1 , and the stirring time is 12 h. After stirring evenly, the temperature-sensitive aqueous electrolyte is obtained.
[0057] The obtained temperature-sensitive aqueous electrolyte was applied to batteries. −2 , 0.2 mAh cm −2 Under the same conditions, the Zn||Zn symmetric battery can be stably cycled for more than 600 h. At 60 °C, 0.4 mA cm −2 , 0.2 mAh cm −2 Under the same conditions, the Zn||Cu asymmetric battery can be stably cycled for more than 100 cycles, and the Coulomb efficiency remains above 99.2%. −1 Under these conditions, the zinc||vanadium pentoxide full battery still has a capacity retention rate of 91.6% after stable cycling for more than 400 cycles.
Claims
1. A method for synthesizing a temperature-sensitive aqueous electrolyte, characterized in that: This method involves dissolving zinc salt in deionized water and stirring it evenly with ultrasonic waves at room temperature to obtain a concentration of 1 to 3 mol L −1 a zinc salt aqueous solution; poloxamer is added to the zinc salt aqueous solution, and mechanical stirring is performed at 0°C. After stirring evenly, a temperature-sensitive aqueous electrolyte is obtained.
2. The method for synthesizing a temperature-sensitive aqueous electrolyte according to claim 1, characterized in that: The zinc salt is one of zinc trifluoromethanesulfonate, zinc chloride, zinc perchlorate, zinc bromide or zinc nitrate.
3. The method for synthesizing a temperature-sensitive aqueous electrolyte according to claim 1, characterized in that: The ultrasonic stirring time is 20 to 30 minutes.
4. The method for synthesizing a temperature-sensitive aqueous electrolyte according to claim 1, characterized in that: The poloxamer is one of Poloxamer 124, Poloxamer 182, Poloxamer 188, Poloxamer 331 or Poloxamer 407, and the mass fraction of the poloxamer in the electrolyte is 15-30%.
5. The method for synthesizing a temperature-sensitive aqueous electrolyte according to claim 1, characterized in that: The mechanical stirring condition refers to a stirring speed of 300-500 r min −1 , stirring time is 12~24 h.
6. A temperature-sensitive aqueous electrolyte synthesized by the method according to any one of claims 1 to 5.
7. The use of a temperature-sensitive aqueous electrolyte according to claim 6, characterized in that: The electrolyte is used in zinc-ion batteries.
8. The use of a temperature-sensitive aqueous electrolyte according to claim 7, characterized in that: The zinc ion battery is one of a zinc||zinc symmetrical battery, a zinc||copper asymmetrical battery or a zinc||vanadium pentoxide full battery.